Characterization of the interactions between Codanin-1 and C15Orf41, two proteins implicated in congenital dyserythropoietic anemia type I disease - Grace Swickley; Yehoshua Bloch; Lidor Malka; Adi Meiri; Sharon Noy-Lotan; Amiel Yanai; Hannah Tamary; Benny Motro (BMC Molecular and Cell Biology, 2020)
Abstract Background Congenital dyserythropoietic anemia type I (CDA I), is an autosomal recessive disease with macrocytic anemia in which erythroid precursors in the bone marrow exhibit pathognomonic abnormalities including spongy heterochromatin and chromatin bridges. We have shown previously that the gene mutated in CDA I encodes Codanin-1, a ubiquitously expressed and evolutionarily conserved large protein. Recently, an additional etiologic factor for CDA I was reported, C15Orf41, a predicted nuclease. Mutations in both CDAN1 and C15Orf41 genes results in very similar erythroid phenotype. However, the possible relationships between these two etiologic factors is not clear. Results We demonstrate here that Codanin-1 and C15Orf41 bind to each other, and that Codanin-1 stabilizes C15Orf41. C15Orf41 protein is mainly nuclear and Codanin-1 overexpression shifts it to the cytoplasm. Phylogenetic analyses demonstrated that even though Codanin-1 is an essential protein in mammals, it was lost from several diverse and unrelated animal taxa. Interestingly, C15Orf41 was eliminated in the exact same animal taxa. This is an extreme case of the Phylogenetic Profiling phenomenon, which strongly suggests common pathways for these two proteins. Lastly, as the 3D structure is more conserved through evolution than the protein sequence, we have used the Phyre2 alignment program to find structurally homologous proteins. We found that Codanin-1 is highly similar to CNOT1, a conserved protein which serves as a scaffold for proteins involved in mRNA stability and transcriptional control. Conclusions The physical interaction and the stabilization of C15Orf41 by Codanin-1, combined with the phylogenetic co-existence and co-loss of these two proteins during evolution, suggest that the major function of the presumptive scaffold protein, Codanin-1, is to regulate C15Orf41 activities. The similarity between Codanin-1 and CNOT1 suggest that Codanin-1 is involved in RNA metabolism and activity, and opens up a new avenue for the study of the molecular pathways affected in CDAI.